Effect of ozone on the formation and breakup of flocs in raw waters with high algae content - (:unkn) unknown (TAYLOR & FRANCIS INC, 2006)
The effect of ozone on the formation, breakup and re-formation of flocs generated using ferric sulphate has been investigated using conventional jar test procedure and by continuous optical monitoring using raw water. Using a range of different dosage of coagulant, the breakage of flocs was followed at a high stirring speed, corresponding to average shear rate (G) of about 518 s(-1). Most of the breakage occurred within a few seconds of increasing the shear rate. After breakage the stirring rate was reduced to the original value of 50 rpm (G approximate to 23 s(-1)) to allow the flocs to re-grow. It was found that only limited re-growth of flocs occurred indicating irreversibility of the floc breakup process. For preozonated samples, the re-growth of flocs occurred to a much greater extent with lower residual turbidity. The findings show that the use of preozonation (1.25 and 1.50 mg/L) provides beneficial results to both improve turbidity removal and reduce coagulant requirement. Furthermore, better re-formation of flocs is achievable.
Keywords: ferric sulphate; floc strength; floc breakage; coagulation; flocculation; ozone; DISSOLVED AIR FLOTATION; PARTICLE-SIZE; FLOCCULATION; OZONATION